2006
DOI: 10.3402/ijch.v65i3.18098
|View full text |Cite
|
Sign up to set email alerts
|

Use of hypnotics in Sámi and non-Sámi populations in northern Norway

Abstract: Objectives. Our knowledge of the impact of indigenous culture on drug consumption is scarce. Based on the Sámi Health Study, we compare the use of hypnotics among the Sámi and non-Sámi people, living in the same area at 70°N in northern Norway. Study Design. Cross-sectional survey based on a cardiovascular screening, including questionnaires and a clinical examination. Methods. A total of 16 323 men and women born 1925 -1967 in counties with a mixed Sámi and non-Sámi population responded to a questionnaire del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…Frequent use of alcohol (two or more time a week) is also higher in the non‐Sámi population. Our results are consistent with earlier publications from the same study (24). Another study among indigenous and non‐indigenous adolescents in northern Norway has found same tendency in drinking patterns, as among adults (25).…”
Section: Discussionsupporting
confidence: 94%
“…Frequent use of alcohol (two or more time a week) is also higher in the non‐Sámi population. Our results are consistent with earlier publications from the same study (24). Another study among indigenous and non‐indigenous adolescents in northern Norway has found same tendency in drinking patterns, as among adults (25).…”
Section: Discussionsupporting
confidence: 94%
“…It is well known that disturbances in emotion regulation and sleep are common aspects of anxiety and depression and that changing quality in sleep is a very sensitive indicator of mental health issues [38]. In the SAMINOR 1 study of Bakken et al [39], with participants mainly from same areas as in the SAMINOR 2 study, the prevalence of insomnia and use of hypnotics in the core Sami group was only half of that in the non-Sami. In the Sami culture, living in accordance with nature is highly valued.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have chosen to classify the participants in four ethnical categories according to Bakken et al [32]. Group 1: Sami 1 : Those who defined themselves as Sami by speaking the Sami language, felt connected to the Sami by speaking their language, or felt affiliated with the Sami (non-ethnic group).…”
Section: Methodsmentioning
confidence: 99%